PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SUBTEMA BENDA DALAM KEGIATAN EKONOMI - Savega Sucitra; Rais Hidayat; Tustiyana Windiyani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the effect of the application of the Problem Based Learning model on the learning outcomes of the object sub-theme in economic activities and to determine differences in the learning outcomes of the object sub-theme in economic activities through the Problem Based Learning and Discovery Learning models in class V SDN Cipayung 4 Depok City. The N-Gain calculation for the Problem Based Learning model is 70 with high criteria, the N-Gain value for the Discovery Learning model is 51 with medium criteria. So that the N-Gain in the experimental class with the Problem Based Learning model is greater than the control class with the Discovery Learning model. The researcher also conducted a normality test with the Fisher test for both samples with normal distribution because the values ​​of the three samples were smaller than Ltable. In the Problem Based Learning class group, the value of Lcount ≤ Ltable was obtained, namely 0.03 ≤ 0.150 and in the Discovery Learning class group, the value of Lcount ≤ Ltable was obtained, namely 0.08 ≤ 0.150. Then in the homogeneity test the data is homogeneous because it is smaller than Ftable, the value is 1.018 ≤ 1.98. Furthermore, in the hypothesis test, the tcount is 2.4987 which is greater than the ttable of 1.9954, indicating that H0 is rejected and Ha is accepted. Thus there is an influence of the Problem Based Learning model on mathematics learning outcomes in data presentation material in class V SDN Cipayung 4.